(untitled) (Acta Scientiarum. Biological Sciences, 2018)
The biological activity of honey has been the subject of great scientific investigation. Bee products are widely used in folk medicine to treat human diseases due to their antibacterial and inhibitory potential action on different human pathogens. Ten honey samples produced by Apis mellifera in the northern of Minas Gerais state were tested against pathogenic microorganisms Staphylococcus aureus TSST (clinical isolated) and enterohaemorrhagic Escherichia coli ATCC 43895 for determination of their minimum inhibitory concentrations. The microdilution technique in broth Mueller-Hinton broth (MHB) was used in four concentrations (25, 12.5, 6.25 and 3.125%). There was a reduction of bacterial growth for the two target species at all concentrations tested. The optimal concentration for inhibition of S. aureus and E. coli were 3.125% (w/v). Therefore, the antibacterial activity of the tested samples evidences the potential of Aroeira honey produced in the north of Minas Gerais for therapeutic use, thus contributing to the aggregation value and commercialization of this type of honey.